PEMBUATAN GAME LAST ORDER MENGGUNAKAN UNITY - Herman Kosasi; Jeanny Pragantha; Rendi Kristyadi (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Game "Last Order" is a Real Time Strategy game genre themed fantasy tale. This game has a background story which players play the role as a commander who got a mission to rescue the princess who was kidnapped by the king of monsters. This game is played using Android mobile devices with two-dimensional graphics. To playing this game, the player must touch the smartphone screen to spawn owned troops to face each stage with different difficulty levels. This game was made using the Unity game engine with C Sharp (C#) programming language. Game testing is performed using  blackbox testing methods, alpha testing by the advisor, and beta testing through a survey of 30 respondents. The test results showed that the appearance of the game is good, interesting  and entertaining to be played.